2021
DOI: 10.1177/0300060521996183
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NEAT1 regulates ferroptosis sensitivity in non-small-cell lung cancer

Abstract: Objectives Ferroptosis is caused by iron-dependent lipid peroxide accumulation, the sensitivity of which might be regulated by acyl-CoA synthetase long chain family member 4 (ACSL4). Non-small-cell lung cancer (NSCLC) can resist oxidative stress and reduce the sensitivity of tumor cells to ferroptosis by changing the expression of some proteins. Mechanisms involving ferroptosis sensitivity in NSCLC are not fully understood. Methods A dual-luciferase reporter assay was used to confirm a targeting relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…Recent reports suggest that ferroptosisrelated lncRNAs play important roles in tumorigenesis, progression, and metastasis via multiple mechanisms. Wu et al [7] reported that lncRNA NEAT1 promoted ferroptosis and ferroptosis sensitivity in non-small-cell lung cancer by regulating the expression of ACSL4. Qi et al [8] reported that lncRNA GABPB1-AS1 could induce ferroptosis in hepatocellular carcinoma cells by inhibiting the translation of GABPB1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that ferroptosisrelated lncRNAs play important roles in tumorigenesis, progression, and metastasis via multiple mechanisms. Wu et al [7] reported that lncRNA NEAT1 promoted ferroptosis and ferroptosis sensitivity in non-small-cell lung cancer by regulating the expression of ACSL4. Qi et al [8] reported that lncRNA GABPB1-AS1 could induce ferroptosis in hepatocellular carcinoma cells by inhibiting the translation of GABPB1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lncRNAs may affect ferroptosis in various ways, and it has been reported that lncRNA GABPB1-AS1 in HCC leads to the downregulation of the gene encoding Peroxiredoxin-5 (PRDX5) peroxidase, suppression of cellular antioxidant capacity, eventual induction of ferroptosis, and high GABPB1-AS1 levels in patients with HCC, which correlated with improved OS (22). Wu et al (23) revealed that lncRNA NEAT1 regulates ferroptosis and ferroptosis sensitivity in non-small-cell lung cancer by targeting acyl-CoA synthetase long-chain family member 4 (ACSL4), which may regulate ferroptosis sensitivity. Seven ferroptosis-related lncRNA signatures were constructed in colon adenocarcinoma (COAD), and the prognostic value of these lncRNAs was con rmed in patients with COAD (24).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of NEAT1 can inhibit the expression of ACSL4, increase the expression of SLC7A11 and GPX4, and reduce the content of regulatory iron in cells. Finally, the occurrence of ferroptosis is decreased, and cell apoptosis is inhibited [204].…”
Section: Lncrnas Regulate the Activity Of Gpx4 In Ferroptosismentioning
confidence: 99%